GEOLOGY, COMPOSITION, CONDITIONS OF FORMATION, AND TECHNIQUE OF EXPLORATION OF THE VLADIMIR GRIB KIMBERLITE PIPE, A NEW DIAMOND DEPOSIT, ARKHANGELSK KIMBERLITE PROVINCE - Verichev E.M.; Garanin V.K.; Kudryavtseva G.P. (My University, 2003)
The paper analyzes the geological structure, mineral parageneses, and composition of minerals of mantle rocks and the kimberlite groundmass, as well as the conditions of formation and the technique, of development of the Vladimir Grib kimberlite pipe, a new diamond deposit in the Arkhangelsk diamondiferous province. The Vladimir Grib pipe is similar in many features to the Yakutian diamondiferous pipes, e.g., Mir and Udachnaya, and differs from the Lomonosov diamond deposit discovered earlier in the Arkhangelsk province. The Vladimir Grib pipe is situated in the central part of the Zimnii Bereg area of the Arkhangelsk province in the Verkhotina field of kimberlites and olivine melilitites. It is expressed as a low-contrast anomaly with an intensity of 9 nT in the local magnetic field. In the surface view, the pipe has a rhomboidal-oval shape and is slightly elongated northeast (25°). The elongation in this direction increases with increasing depth, and the pipe attains pear-shaped contours with a narrower southward termination. In vertical section, the pipe is a cone-shaped body flaring upward. The pipe was formed in several stages. Four stages were distinguished for the crater-facies rocks and two stages for the diatreme-facies rocks. The rocks of the hypabyssal facies have not yet been studied, and deep drilling (>1000 m) is being performed now. The yield of the heavy mineral fraction is normally high (up to 50 kg/t). The fraction is dominated by ilmenite (picroilmenite), pyrope-almandine, pyrope, phlogopite, and clinopyroxene, while olivine and orthopyroxene occur in minor amounts. Chrome spinel contents are very low. The rocks of the Vladimir Grib pipe differ from kimberlites of the pipes of the Lomonosov deposit by higher (by 30-50 times) contents of intratelluric minerals, dominated by picroilmenite. The pipe belongs to the magnesian type of kimberlites (25-37 wt % MgO). The rocks have low Al2O3 (2.3 wt %, on average) and alkali contents and show the lowest contamination indices among the pipes of the Arkhangelsk province. K2O dominates over Na2O (0.03-1.38 against 0.01-0.74 wt %). The rocks of the pipe have low contents of trace and rare earth elements. Low Ce/Y and Zr/Nb ratios of kimberlites of the Vladimir Grib pipe may indicate elevated degrees of melting of their mantle source, probably, garnet-spinel peridotite with a low degree of metasomatic transformation. The diamond potential of the Vladimir Grib pipe is much higher than that of any pipe of the Lomonosov deposit. The diamonds are characterized by a larger proportion of octahedral crystals, particularly in coarser fractions (>2 mm); a low proportion of dodecahedra (D); and large proportions of transitional forms (O-D), cubes, and pseudohemimorphic stones. The amount of tetrahexahedral crystals is three orders of magnitude lower than in pipes of the Lomonosov deposit. Parageneses of various types are revealed for olivine, garnet, clino- and orthopyroxenes, and ilmenite. The heavy mineral fractions contain large proportions of minerals that could associate with diamonds. Kimberlites contain abundant xenoliths of various metamorphic crustal and mantle rocks. Some of them have pegmatoid texture and consist of megacrysts of Cr-Ti pyrope, picroilmenite, chrome diopside, and phlogopite. Eclogites do not exceed 10% of mantle xenoliths. Aluminous eclogite xenoliths have not been found. Crustal xenoliths are dominated by garnet-bearing schists. PT conditions of formation were calculated for mantle xenoliths according to garnet-clinopyroxene assemblages using a self-consistent system of geothermometers and geobarometers. PT parameters obtained for pyrope peridotites (T = 1000-1250°C, P = 38-46 kbar) and eclogites (T = 950-1050°C, P = 35-39 kbar) indicate rock formation near graphite-diamond boundary conditions. Mineral assemblages of crustal (eclogite-like) rocks indicate their crystallization under conditions of garnet-pyroxene-plagioclase metamorphic facies of metabasites (T = 800-900°C, P = 6-9 kbar). The megacrysts were dated at 990 Ma, which is much older than the kimberlites (Late Devonian-Middle Carboniferous by flora remnants in the rocks of the pipe). The following evolutionary (but discrete) process of mantle rock formation is suggested: crystallization of rocks of diamondiferous association (stage I); crystallization of peridotites, pyroxenites, and eclogites (stage II); and formation of pegmatoid rocks including megacrysts and metasomatized peridotites and pyroxenites (stage III). The commercial diamond reserves are verified to the depth of 610 m, and P1 resources are estimated to the depth of 1030 m. It is suggested that the main reserves be developed by underground mining and then the remaining reserves be recovered by a small open pit. The proposed concept can be also used for the development of the Lomonosov deposit.